ASPEK HUKUM TERHADAP INTERKONEKSI GIZI, KESEHATAN, DAN PENDIDIKAN: MEWUJUDKAN SDGS MELALUI KEBIJAKAN MAKANAN BERGIZI GRATIS DI SEKOLAH - Imanuel Inriyanto Ruslak Hammar; Yunus Tekad Kurniadi Ruslak Hammar; Bernardus Horokubun (PATRIOT, 2025)
The provision of free healthy meals within school environments is one of the government’s policy measures aimed at strengthening the foundation of human resource quality from an early age, particularly at the elementary school level. This policy is rooted not only in social and public health imperatives but also carries significant legal dimensions, as it directly relates to the fulfillment of fundamental rights of citizens—especially the rights to food, healthcare, and quality education. This paper explores the legal framework underlying the interconnection between nutritional fulfillment, health conditions, and access to education within the context of the Sustainable Development Goals (SDGs), with a particular focus on Goal 2 (Zero Hunger) and Goal 4 (Quality Education). A normative juridical approach is employed to examine several regulations, including the 1945 Constitution, Law No. 36 of 2009 on Health, Law No. 18 of 2012 on Food, and Presidential Regulation No. 59 of 2017 concerning the implementation of the SDGs. The findings indicate that the provision of nutritious food free of charge represents a tangible manifestation of the state's role in fulfilling socio-economic rights within a legal state framework. However, its implementation remains hampered by institutional challenges, weak oversight mechanisms, and limited cross-sectoral coordination. Therefore, regulatory synergy across sectors is essential to ensure the inclusive and sustainable realization of the SDGs.